Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2016)
Conventional tillage resulted in greater corn yield in 2015 than with reduced tillage or no-till. A tillage × N fertilizer treatment interaction showed that N placement did not affect corn yield in conventional or reduced tillage systems, but subsurface knife N placement in no-till resulted in greater yield than when N was surface-applied.
Keywords: crops